The effect of different nitrogen sources on mycelial growth of oyster mushroom, Pleurotus ostreatus : with a review concerning cultivation of the species - Laursen, Astrid (SLU/Dept. of Biosystems and Technology (from 130101), 2018)
The production of Oyster mushroom, Pleurotus ostreatus, is sustainable, both in terms of economy and environment. Cultivation can be performed successfully on a wide range of substrates, often in the form of otherwise non-productive waste from other industries, such as agriculture and forest production.